2015
DOI: 10.1038/ncomms9509
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired electron-delivering system for reductive activation of dioxygen at metal centres towards artificial flavoenzymes

Abstract: Development of artificial systems, capable of delivering electrons to metal-based catalysts for the reductive activation of dioxygen, has been proven very difficult for decades, constituting a major scientific lock for the elaboration of environmentally friendly oxidation processes. Here we demonstrate that the incorporation of a flavin mononucleotide (FMN) in a water-soluble polymer, bearing a locally hydrophobic microenvironment, allows the efficient reduction of the FMN by NADH. This supramolecular entity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Therefore, based on the structural features that, like widely existed microbial P450s, lack the reductase domain, we chose this microbial P450 as a model enzyme to probe its cofactor requirement, particu-13 larly whether riboflavin could substitute classic redox partner for the catalysis based on previous observations. [12][13][14][15][16] Surprisingly, HmtS indeed could directly utilize riboflavin and NADPH to accomplish the N-delakylation, showing higher efficiency than FAD and FMN. Further thorough comparison revealed that this finding is mediated by a new electron transfer pathway, which is not the same as any reported mechanisms for P450s.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the structural features that, like widely existed microbial P450s, lack the reductase domain, we chose this microbial P450 as a model enzyme to probe its cofactor requirement, particu-13 larly whether riboflavin could substitute classic redox partner for the catalysis based on previous observations. [12][13][14][15][16] Surprisingly, HmtS indeed could directly utilize riboflavin and NADPH to accomplish the N-delakylation, showing higher efficiency than FAD and FMN. Further thorough comparison revealed that this finding is mediated by a new electron transfer pathway, which is not the same as any reported mechanisms for P450s.…”
Section: Discussionmentioning
confidence: 99%
“…Modified polyethyleneimines (PEI) are water‐soluble polymers known as good mimics for the local hydrophobic microenvironment of an enzyme′s active site . Using PEI modified with guanidinium and octyl groups, we previously showed that the incorporation of flavin mononucleotide (FMN) into such a microenvironment generated artificial flavoenzymes capable of collecting electrons from nicotinamide adenine dinucleotide (NADH) and then of reducing metallic cofactors under anaerobic conditions . Here, we demonstrate that under aerobic conditions, similar artificial flavoenzymes made of FMN incorporated into PEI, modified with guanidinium and octyl groups (FMN‐PEI guan‐oct ; Scheme ), catalyze the oxidation of NADH and perform aerobic BV reactions in water.…”
Section: Methodsmentioning
confidence: 99%
“…The FMN cofactor was then incorporated into the polymer thanks to the specific electrostatic interaction between the negatively charged phosphate groups and the guanidinium moieties. This incorporation of the FMN into the confined hydrophobic environment of the polymer was monitored by UV/Vis absorption spectroscopy, showing a characteristic 10 nm hypsochromic shift of the FMN band at 370 nm (Figure ) . Importantly, we also measured the absorption spectrum of FMN‐PEI guan‐oct in the presence of an excess of bicylo[3.2.0]hept‐2‐en‐6‐one as a potential substrate, and the same 10 nm shift was observed (Figure , red trace).…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the challenge of providing the necessary electrons without quenching the active species, most synthetic systems use H 2 O 2 (hydrogen peroxide) as oxidizing agent and thus avoid the NADH/FMN couple altogether. Using a water‐soluble polyethyleneimine (PEI) polymer incorporating FMN units, Avenier and Mahy showed that a synzyme (synthetic enzyme) could be created to perform the role of a reductase enzyme . The PEI polymer is derivatized with guanidinium and octyl groups, thus offering binding for the FMN phosphate group while inducing a local hydrophobic environment.…”
Section: Combined Flavin/nad(p)h Manifoldsmentioning
confidence: 99%